2019
DOI: 10.1049/ccs.2019.0007
|View full text |Cite
|
Sign up to set email alerts
|

Disentanglement in conceptual space during sensorimotor interaction

Abstract: The disentanglement of different objective properties from the external world is the foundation of language development for agents. The basic target of this process is to summarise the common natural properties and then to name it to describe those properties in the future. To realise this purpose, a new learning model is introduced for the disentanglement of several sensorimotor concepts (e.g. sizes, colours and shapes of objects) while the causal relationship is being learnt during interaction without much a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature by Marchetti et al (2018) showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008 ; Itakura et al, 2008 ; Moriguchi et al, 2011 ; Kannegiesser et al, 2015 ; Okanda et al, 2018 ; Di Dio et al, 2019 ; Wang et al, 2020 ; Manzi et al, 2020a ) and developmental robotics (DR; De La Cruz et al, 2014 ; Cangelosi and Schlesinger, 2015 , 2018 ; Lyon et al, 2016 ; Morse and Cangelosi, 2017 ; Vinanzi et al, 2019 ; Zhong et al, 2019 ; Di Dio et al, 2020a , b ). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people’s behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our method is highly compatible with conventional self-supervised learning focusing on geometric problems, and when combined with conventional methods, it is expected to enable more complex and dynamic behaviors, depending on the environment and situation. In recent years, research has been conducted to understand concepts such as color and shape in language and images from the physicality of the robot using selfsupervised learning [55]. Further development of the proposed method may lead to the understanding of complex and abstract concepts correlated with speed, such as "fast or slow," "strong or weak," and "heavy or light," through the dynamic body movements of the robot.…”
Section: ) Resultsmentioning
confidence: 99%
“…A recent review of the literature by showed that different physical characteristics of HSRs may significantly affect the quality of interaction between humans and robots at different ages. The construction of robots that integrate and expand the specific biological abilities of our species led to two different directions in robotic development based on different, though related, theoretical perspectives: developmental cybernetics (DC; Itakura, 2008;Moriguchi et al, 2011;Kannegiesser et al, 2015;Okanda et al, 2018;Wang et al, 2020;Manzi et al, 2020a) and developmental robotics (DR;De La Cruz et al, 2014;Schlesinger, 2015, 2018;Lyon et al, 2016;Morse and Cangelosi, 2017;Zhong et al, 2019;Di Dio et al, 2020a,b). The first perspective (DC) consists of creating a human-like system, by simulating human psychological processes and prosthetic functions in the robot (enhancing the function and lifestyle of persons) to observe people's behavioral response toward the robot.…”
Section: Introductionmentioning
confidence: 99%